Durability of Concrete Wall Panel with Fibers Using Non- Autoclaved Aerated Technique(Cowap-FINAT) - Azizul Mustaqim Abdul Latiff; Lutfil Hazim Selamat Sainudin; Mohamad Fazrul Monkahar; Nur’ Ain Idris (Multidisciplinary Applied Research and Innovation, 2024)
Wall is an element that play a big role in construction of house, building and other. The purposes of walls in buildings are to support roofs, floors and ceilings, to enclose a space as part of the building envelope along with a roof to give buildings form and to provide shelter and security.Standard wall panel usually built at construction site.The disadvantage of this method is it cost more, take a lot of time, quality will less controlled etc. In this study, Industrialized Building System (IBS) which means a technology of construction which there are manufactured in controlled environment, either at off site or site.The objectives are to determine the suitable ratio of non-autoclaved aerated concrete (NAAC) and to investigate the best ratio of mixed natural and glass fiber in aerated concrete that give higher strength,to build wall panel based on the best ratio of mixed fiber in non-autoclaved aerated concrete (NAAC).Methodology of this study starts with preparation of both fiber which is treatment,shredding and mixing. Experimental work begun with concrete cube preparation,concrete mix design and fiber ratio and compressive strength test for cube followed with rebound hammer test for wall panel.The percentage compressive strength of AC with 25% of AP is 1.643Mpa. AC 60% fiber glass 40% bamboo fiber with 1.643 Mpa of compressive strength. The average result rebound hammer for aerated wall panel is 11.5. In conclusion, this study can prove that modified wall panel still with lightweight concrete with reduction of 58% of weight from standard concrete which were 2.25 kg to 0.943kg but still has a good compressive strength. However, its still not strong enough to be used in construction industry due to several factors.